Promoting portuguese as foreign language teaching mediated by multimodal textes in extension practices - Kfouri, Marta Lucia Cabrera[UNESP] (Unesp-faculdade Ciencias & Letras, 2021)
In this article, we present some results of the use of multimodal texts in teaching Portuguese as a Foreign Language (PFL) offered in an extension project at a public university. Participants are foreigners from different countries, in a situation of academic and social immersion in the city where the university is located. The objective is to characterize the multimodal text as a resource for intercultural and humanizing experiences of meaningful language learning (COSTA VAL, 2004), especially worked in a group on the social network Facebook. The results suggest that, although it has no educational purposes, the social network in question revealed itself as an environment with potential for the humanization of learning, due to its possibilities of interaction, socialization and communication in the target language, functioning as an intercultural and learning tool. collaborative online (FINARDI and PORCINO, 2016). The use of multimodal texts, due to their characteristics, promoted high connectivity and expansion between contents already worked on in classes and other complementary ones.
Keywords: Portuguese as foreign language; Multimodal texts; Intercultural and humanizing teaching; Extension project; Public university